Tissue localization of piscidin host-defense peptides during striped bass (Morone saxatilis) development. Issue 61 (February 2017) - Salger, Scott A.; Reading, Benjamin J.; Noga, Edward J.
Abstract: Infectious diseases are a major cause of larval mortality in finfish aquaculture. Understanding ontogeny of the fish immune system and thus developmental timing of protective immune tissues and cells, may help to decrease serious losses of larval fishes when they are particularly vulnerable to infection. One component of the innate immune system of fishes is the host-defense peptides, which include the piscidins. Piscidins are small, amphipathic, α-helical peptides with a broad-spectrum of action against viral, bacterial, fungal, and protozoan pathogens. We describe for the first time the cellular and tissue localization of three different piscidins (1, 3, and 4) during striped bass ( Morone saxatilis ) larval ontogeny using immunofluorescent histochemistry. From 16 days post hatch to 12 months of age, piscidin staining was observed in cells of the epithelial tissues of gill, digestive tract, and skin, mainly in mast cells. Staining was also seen in presumptive hematopoietic cells in the head kidney. The three piscidins showed variable cellular and tissue staining patterns, possibly relating to differences in tissue susceptibility or pathogen specificity. This furthers our observation that the piscidins are not a monolithic family of antimicrobials, but that different AMPs have different (more specialized) functions. Furthermore, no immunofluorescent staining of piscidins was observed in post-vitellogenic oocytes, embryos, or larvae from hatch to 14 days post hatch, indicating that this critical component of the innate immune system is inactive in pre-hatch and young larval striped bass. Highlights: The ontogeny of the host-defense peptides, piscidins, was investigated. Piscidins first appear in the striped bass between 14 and 16 dph. Piscidins showed variable cellular and tissue staining patterns. Could relate to differences in tissue susceptibility or pathogen specificity. Supports observations that each piscidin has different (specialized) functions.